Facial Balamuthia mandrillaris infection with neurological involvement in an immunocompetent child. Issue 3 (March 2022) - Zhang, Zhen; Liang, Jianying; Wei, Ruoqu; Feng, Xiaobo; Wang, Lei; Wang, Liuhui; Zhao, Piaoping; Yu, Hong; Gu, Yan; Yao, Zhirong
Summary: Cutaneous infection by Balamuthia mandrillaris is a rare condition that is sometimes complicated by life-threatening CNS involvement. It often evades timely diagnosis due to its rarity and non-specific clinical manifestations. Patients can be either immunocompetent or immunocompromised. It is probably transmitted via inhalation or inoculation through broken skin, and then spreads to the brain and other organs through haematogenous spread. It is important for clinicians to be aware of this disease because rapid diagnosis and subsequent therapy has, in some cases, been associated with survival. In this Grand Round, we report the case of a 7-year-old boy who presented with large, chronic plaques on his face. Several biopsies showed non-specific granulomatous inflammation. The patient deteriorated rapidly and died within 1 month of displaying abnormal symptoms in the CNS. Immunohistochemical staining of skin tissue identified B mandrillaris as the infectious agent. The diagnosis was confirmed with PCR, which detected B mandrillaris DNA in formalin-fixed skin tissue sections. B mandrillaris infection should be considered in the differential diagnosis of patients with chronic granulomatous lesions. We also reviewed the epidemiology, B mandrillaris in nature and in the laboratory, clinical manifestations, histopathology, diagnosis, and treatment of infection.